Antibacterial Properties of Mussel-Inspired Polydopamine Coatings Prepared by a Simple Two-Step Shaking-Assisted Method - Kord Forooshani, Pegah; Polega, Elizabeth; Thomson, Kevin; Bhuiyan, Md. Saleh Akram; Pinnaratip, Rattapol; Trought, Mikhail; Kendrick, Chito; Gao, Yuesheng; Perrine, Kathryn A.; Pan, Lei; Lee, Bruce P. (Frontiers in Chemistry, 2019)
A simple two-step, shaking-assisted polydopamine (PDA) coating technique was used to impart polypropylene (PP) mesh with antimicrobial properties. In this modified method, a relatively large concentration of dopamine (20 mg mL-1) was first used to create a stable PDA primer layer, while the second step utilized a significantly lower concentration of dopamine (2 mg mL-1) to promote the formation and deposition of large aggregates of PDA nanoparticles. Gentle shaking (70 rpm) was employed to increase the deposition of PDA nanoparticle aggregates formation a thicker PDA coating with nano-scaled surface roughness (RMS = 110 nm and Ra = 82 nm). Cyclic voltammetry experiment confirmed that the PDA coating remained redox active, despite extensive oxidative crosslinking. When PDA-coated mesh was hydrated in phosphate saline buffer (pH 7.4), it was activated to generate 200 µM hydrogen peroxide (H2O2) for over 48h. The sustained release of low doses of H2O2 was antibacterial against both gram-positive (Staphylococcus epidermidis) and gram-negative (Escherichia coli) bacteria. PDA coating achieved 100% reduction (LRV ~3.15) when incubated against E. coli and 98.9% reduction (LRV ~1.97) against S. epi in 24h.